2014
DOI: 10.1097/mlr.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care and Specialty Providers

Abstract: Regardless of the predominant provider's specialty, greater continuity was associated with less use of high-cost services and lower expenditures for these services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 18 publications
1
32
1
Order By: Relevance
“…Most of the previous studies used claims data from health insurance reimbursement databases [36, 11, 42]. Moreover, the outcomes of these studies focused on health resource utilization (hospitalizations and emergency department visits) and healthcare expenses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies used claims data from health insurance reimbursement databases [36, 11, 42]. Moreover, the outcomes of these studies focused on health resource utilization (hospitalizations and emergency department visits) and healthcare expenses.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of continuity of care have been debated in previous studies because some have concluded that continuity of care is associated with fewer hospitalizations, emergency department visits, and hospital admissions [37]; low pharmaceutical expenditures and healthcare expenses [5, 8–10]; decreased mortality rates [11, 12]; fewer duplicated medications [13]; improved medication adherence [14]; and patient satisfaction [15–18]. However, others insist that high continuity of care may lead to the purchase of more drugs overall and that the effects on HRQoL are unclear; thus, these should be further examined [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies focus solely on care delivered by PCPs (Wasson 1984;Menec et al 2006;Wolinsky et al 2010;Katz, McCoy, and Vaughan-Sarrazin 2015), while those that allow for inclusion of specialists do not test for a separate effect (Weiss and Blustein 1996;Gill and Mainous 1998;Nyweide et al 2013;Hussey et al 2014;Romano, Segal, and Pollack 2015). Only 1 of the 13 identified studies tests for any separate specialist effect, and it finds that effect to be beneficial for reducing inpatient and ED utilization but it does not address health outcomes or distinguish between disease-relevant and other types of specialists (Romaire et al 2014). The prior research on specialist involvement in chronic illness care is mixed.…”
Section: Structure (Year T-1)mentioning
confidence: 99%
“…A line of research stretching back to the 1980s finds beneficial associations between higher COC and lower probability of inpatient and/or emergency department (ED) utilization (van Walraven et al 2010). However, more recently, a study of Medicare beneficiaries found increased incidence of ambulatory care-sensitive (ACS) hospitalization for those with higher COC (Romaire et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation